1990
DOI: 10.1111/j.2042-3306.1990.tb04199.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phenothiazine on plasma prolactin levels in non‐pregnant mares

Abstract: Summary Sixteen non‐pregnant pony mares were divided into four groups of similar age and bodyweight (bwt). Groups were randomly assigned to one of four treatments consisting of oral administration of perphenazine (0.5 and 1.0 mg/kg bwt, phenothiazine (10 mg/kg bwt) and a control group. Blood samples were taken by jugular venepuncture and plasma prolactin concentrations measured using an homologous assay for equine prolactin. Analysis of variance was conducted on data designed as a split plot over time. Perphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Johnson and Becker [38] were the first to confirm that, in fact, administration of bromocriptine, a dopamine agonist, reduced serum prolactin concentrations in horses in May, when concentrations were high, and that two dopaminergic antagonists, metoclopramide and sulpiride, each alone stimulated an immediate response in serum prolactin concentrations. Subsequent reports of the use of perphenazine [45,46] and domperidone [47] in mares confirmed their stimulatory effects on prolactin secretion in the short term. Repeated daily injections of sulpiride in vegetable shortening (to slow its release) to stallions for 14 days in winter [40] increased plasma prolactin concentrations in daily blood more than sixfold, to levels comparable to those normally found in stallions in summer.…”
Section: Dopaminergic and Antidopaminergic Compoundsmentioning
confidence: 73%
“…Johnson and Becker [38] were the first to confirm that, in fact, administration of bromocriptine, a dopamine agonist, reduced serum prolactin concentrations in horses in May, when concentrations were high, and that two dopaminergic antagonists, metoclopramide and sulpiride, each alone stimulated an immediate response in serum prolactin concentrations. Subsequent reports of the use of perphenazine [45,46] and domperidone [47] in mares confirmed their stimulatory effects on prolactin secretion in the short term. Repeated daily injections of sulpiride in vegetable shortening (to slow its release) to stallions for 14 days in winter [40] increased plasma prolactin concentrations in daily blood more than sixfold, to levels comparable to those normally found in stallions in summer.…”
Section: Dopaminergic and Antidopaminergic Compoundsmentioning
confidence: 73%
“…Group A (n = 4) received bromocriptine (Sigma Chemical Co.. St. Louis, MO, USA) intramuscularly at 07:00 and 17:00 h at 0-08 mg/kg body weight0'75 per day beginning on Day 295 of gestation and continuing until parturition; this dose was based on the data of Johnson & Becker (1987). Group ( = 4) received the same treatment as Group A with the addition of oral perphenazine (Sigma) at 0-375 mg/kg body weight twice a day at 07:00 and 17:00 h beginning on Day 305 of gestation and continuing until parturition; the dose was based on a previous experiment from this laboratory (Loch et al, 1990). Group C (n = 3) received an intramuscular injection of saline (0-9% NaCl, w/v) equivalent in volume to the injections given to mares in Group A.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study it has been reported that the hyperprolactinemic effect of chlorpromazine in pre-pubertal rats results in loss of follicles due to atresia and it also delayed the development of follicles. Thus, those changed might occurred (2,12) due to that the dopamine antagonists (chlorpromazine) which increased serum prolactin level to be more than the normal level which in turn caused reverse effects instead of increasing the development follicle, hence it is well known that prolactin plays a role on sexual maturation 20 , development of follicles, ovarian function 21 and plays a major roles in regulating implantation 22-24 . Freeman et al (2000) 25 has been reported that hyperprolactinemia induced infertility in rats and human which can be result from various physiological and pathological conditions such as breast-feeding, prolactin secreting pituitary tumors, or hypothyroidism.…”
Section: Discussionmentioning
confidence: 95%
“…It is well established that chlorpromazine a dopaminergic receptor antagonist 6,7 , raised blood prolactin concentration causing hyperprolactinaemea in human and other mammals [8][9][10][11][12] . Similarly in the present study treatment with chlorpromazine caused significant increase in serum prolactin level in immature female rats compared to the initial control as well as the control.…”
Section: Discussionmentioning
confidence: 99%